Identification and Intervention for Primary Pupils with Dyslexia in Ireland and England: Finding a Path Through the Maze - McPhillips, Thérese; Bell, Sheena; Doveston, Mary (REACH: Journal of Inclusive Education in Ireland, 2021)
Both within Ireland and England there is concern from government level down about how to address literacy standards in primary schools in general and to improve support for learners with dyslexia/specific learning difficulties. This article draws on data that was collected in Ireland and England and compares the provision and organisation of dyslexia support and the role of specialised staff. Identification, assessment, programmes and materials used in overcoming barriers to learning are also discussed.